Aspekty socjalne Unii Europejskiej - Kalina-Prasznic, Urszula (Social Aspects of the European Union, 2006)
Integration processes in Europe are at the same time the history of coherence and contradiction between economic and social goals. On the one hand, integration is aimed at creating uniform European market with unhindered competition. On the other hand, integration aims to make working and living and living conditions within this territory correspond with jointly agreed standards, and not a consequence of the market game only. Initial notion of a swift "automatic" social coherence, which would be the anticipated result of the common market, was replaced with the conviction of a long-term and gradual evolution of the process. The problem of nonparallelism of economic and social integration processes (contradictions arising therefrom) kept increasing with the territorial expansion of the Community. Nowadays, activities aimed at decreasing the asymmetry in development of economic and social integration are based on "the europeanisation of social policies" in the member states (among others, the open method of cooperation is used for that purpose) rather than on the intensification of over national union social policy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 17-25